Bank exposures and sovereign stress transmission - Carlo Altavilla; Marco Pagano; Saverio Simonelli (Goethe University Frankfurt, Center for Financial Studies (CFS), 2016)
Using novel monthly data for 226 euro-area banks from 2007 to 2015, we investigate the determinants of changes in banks' sovereign exposures and their effects during and after the crisis. First, public, bailed out and poorly capitalized banks responded to sovereign stress by purchasing domestic public debt more than other banks, with public banks' purchases growing especially in coincidence with the largest ECB liquidity injections. Second, bank exposures significantly amplified the transmission of risk from the sovereign and its impact on lending. This amplification of the impact on lending does not appear to arise from spurious correlation or reverse causality.
urn:nbn:de:hebis:30:3-416210
Keywords: E44; F3; G01; G21; H63; 330; sovereign exposures; sovereign risk; bank lending; credit risk; euro; crisis